Association of preoperative anaemia with postoperative morbidity and mortality: an observational cohort study in low-, middle-, and high-income countries. (December 2018) - Fowler, A.J.; Ahmad, T.; Abbott, T.E.F.; Torrance, H.D.; Wouters, P.F.; De Hert, S.; Lobo, S.M.; Rasmussen, L.S.; Della Rocca, G.; Beattie, W.S.; Wijeysundera, D.N.; Pearse, R.M.; et al.
Abstract: Background: Anaemia is associated with poor postoperative outcomes, but few studies have described the impact of preoperative anaemia in low- and middle- (LMICs), and high-income countries (HICs). Methods: This was a planned analysis of data collected during an international 7 day cohort study of adults undergoing elective inpatient surgery. The primary outcome was in-hospital death, and the secondary outcomes were in-hospital complications. Anaemia was defined as haemoglobin <12 g dl −1 for females and <13 g dl −1 for males. Hierarchical three-level mixed-effect logistic regression models were constructed to examine the associations between preoperative anaemia and outcomes. Results: We included 38 770 patients from 474 hospitals in 27 countries of whom 11 675 (30.1%) were anaemic. Of these, 6886 (17.8%) patients suffered a complication and 198 (0.5%) died. Patients from LMICs were younger with lower ASA physical status scores, but a similar prevalence of anaemia [LMIC: 5072 (32.5%) of 15 585 vs HIC: 6603 (28.5%) of 23 185]. Patients with moderate [odds ratio (OR): 2.70; 95% confidence interval (CI): 1.88–3.87] and severe anaemia (OR: 4.09; 95% CI: 1.90–8.81) were at an increased risk of death in both HIC and LMICs. Complication rates increased with the severity of anaemia. Compared with patients in LMICs, those in HICs experienced fewer complications after an interaction term analysis [LMIC (OR: 0.92; 95% CI: 0.87–0.97) vs HIC (OR: 0.86; 95% CI: 0.84–0.87); P <0.01]. Conclusions: One-third of patients undergoing elective surgery are anaemic. These patients have an increased risk of complications and death. The prevalence of anaemia is similar amongst patients in LMICs despite their younger age and lower risk profile. Clinical trial registration: ISRCTN51817007.